Cost‐effectiveness analysis of the new oncological drug durvalumab in Italian patients with stage III non‐small cell lung cancer. Issue 19 (15th August 2022) - Buja, Alessandra; Pasello, Giulia; Schiavon, Marco; De Luca, Giuseppe; Rivera, Michele; Cozzolino, Claudia; De Polo, Anna; Scioni, Manuela; Bortolami, Alberto; Baldo, Vincenzo; Conte, PierFranco
Abstract: Background: The monoclonal antibody durvalumab, an immune‐checkpoint inhibitor (ICI) antiprogrammed death ligand 1 (PD‐L1), is available for unresectable stage III NSCLC patients as consolidation therapy following induction chemoradiotherapy, with very promising overall survival (OS) and progression‐free survial (PFS) results in registration trials. The purpose of this study was to provide policymakers with an estimate of the cost‐effectiveness of durvalumab in the treatment of non‐small cell lung cancer (NSCLC). Methods: The study developed a Markov model covering a 5‐year period to compare costs and outcomes of treating PD‐L1 positive patients with or without durvalumab. We conducted a series of sensitivity analyses (Tornado analysis and Monte Carlo simulation) by varying some parameters to assess the robustness of our model and identify the parameters with the greatest impact on cost‐effectiveness. Results: Prior to the release of durvalumab, the management of NSCLC over a 5‐year period cost €33 317 per patient, with an average life expectancy of 2.01 years. After the introduction of the drug, this increased to €37 317 per patient, with an average life expectancy of 2.13 years. Treatment with durvalumab led to an incremental cost‐effectiveness ratio (ICER) of €35 526 per year. OS is the variable that contributes the most to the variability of the ICER. Conclusions: The study observed that durvalumab is a cost‐effective treatment option for patients with unresectable stage III NSCLC. Abstract : Treatment with Durvalumab led to an incremental cost‐effectiveness ratio (ICER) of 35, 526 per year. This study demonstrated that Durvalumab therapy could be cost‐effective for patients with unresectable stage III NSCLC at a willingness‐to‐pay (WTP) threshold of €50, 000 per life year gained.